Composite magnesium cement and alkali-activated slag road surface rapid repair mortar and preparation method thereof
By using hydrated intermediate products in magnesium phosphate cement to react with nanocolloidal silica, and stimulating domestic waste incineration slag to form a high water resistance C-A-S-H gel, the problems of short settling time and poor water resistance in road repair are solved, and the effects of improving water resistance and extending settling time are achieved.
Patent Information
- Application Number
- CN202311798025.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-12-25
AI Technical Summary
The existing magnesium phosphate cement has problems such as too short settling time and poor water resistance in road surface repair applications, which limits its application in humid environments.
Potassium silicate and sodium silicate are generated by reacting hydrated intermediates of magnesium phosphate gelling materials with nanocolloidal silica, and slag of domestic waste incineration is stimulated to form a C-A-S-H gel with high water resistance.
It effectively improves the water resistance of magnesium phosphate gelling materials, delays the setting time of cement, and utilizes domestic waste incinerator slag to realize the development concept of green and environmental protection.
Smart Images

Figure CN117800702B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering building materials, and in particular is a rapid road repair mortar of composite magnesium cement and alkali-activated slag and a preparation method thereof. Background Art
[0002] With the sharp increase in road traffic volume and axle load, coupled with the damage of complex climate environment, many concrete pavements have a large number of potholes, which seriously affect the bearing capacity of the pavement and driving safety. Potassium magnesium phosphate cement is widely used in rapid engineering repair, solidification of heavy metals and radioactive waste, etc. due to its advantages such as early strength and fast hardening, excellent bonding performance and good volume stability. As a rapid pavement repair material, it needs to be used in humid or rainy areas. However, magnesium phosphate cement has problems such as short setting time and poor water resistance, which will limit the application of magnesium phosphate cement in pavement repair.
[0003] Application publication number CN115818993A invented a water-resistant magnesium phosphate cement and a preparation method thereof, which uses Pomacea canaliculata shell powder and the remaining soluble phosphate in the hardened magnesium phosphate cement to generate calcium hydrogen phosphate, reduces the dissolution of soluble phosphate and its filling effect, thereby improving the strength and water resistance of magnesium phosphate cement, and increasing the economic added value of Pomacea canaliculata shell powder. However, the patent is only for the purpose of using Pomacea canaliculata shell powder and the remaining soluble phosphate to generate calcium hydrogen phosphate, which can be achieved in materials containing active calcium. The effect of improving water resistance depends more on the consumption of excess soluble phosphate and the filling effect, and the problem of poor water resistance of the hydration product of magnesium cement itself has not been effectively solved.
[0004] Authorization announcement number CN113816635B invented a fast-hardening, early-strength, highly water-resistant magnesium phosphate-alkali-activated mixed cementitious material. The patent uses the product (potassium hydroxide) of magnesium phosphate cementitious material after water action as an activating substance to alkali-activate the activatable minerals, thereby forming a mixed system in which magnesium phosphate cementitious material and alkali-activated cementitious material coexist, thereby improving the water resistance of magnesium phosphate cement. However, the patent uses a single phosphate (dipotassium hydrogen phosphate), which is relatively expensive. The activatable minerals used are any one or more of slag, volcanic ash, and fly ash, while this patent uses waste incineration slag to replace the above-mentioned activating minerals, which has lower costs and better environmental effects, and seeks new application scenarios for waste incineration slag. In addition, the patent adds water-absorbent resins and porous water-absorbent materials (such as ceramsite, etc.). After the water return is completed, the porosity of the material is bound to increase, resulting in a decrease in the mechanical properties of the matrix and a deterioration in the impermeability, thereby affecting the water resistance of the material.
[0005] To this end, the present invention provides a composite magnesium cement and alkali-activated slag pavement rapid repair mortar and a preparation method thereof, which utilizes the hydration intermediate products (potassium hydroxide and sodium hydroxide) of magnesium phosphate cementitious materials to react with nano-colloidal silica to generate potassium silicate and sodium silicate, and activates domestic waste incineration slag to generate highly water-resistant CASH gel, which not only effectively utilizes domestic waste incineration slag, practices the concept of green and environmentally friendly development, but also improves the water resistance of magnesium phosphate cementitious materials. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a composite magnesium cement and alkali-activated slag pavement rapid repair mortar and a preparation method thereof, so as to improve the water resistance of magnesium phosphate cementitious materials and delay the setting time of magnesium phosphate cement.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0008] A composite magnesium cement and alkali-activated slag road surface rapid repair mortar, wherein the composite magnesium cement and alkali-activated slag road surface rapid repair mortar uses a composite system of magnesium phosphate cementitious material and alkali-activated cementitious material as a cementitious material;
[0009] The magnesium phosphate gelling material is composed of dead-burned magnesium oxide, dipotassium hydrogen phosphate and disodium hydrogen phosphate;
[0010] The alkali-activated gelling material is composed of potassium silicate and sodium silicate generated by the reaction of activated domestic waste incineration slag and hydration intermediate products (potassium hydroxide and sodium hydroxide) of magnesium phosphate gelling material with nano-colloidal silicon dioxide;
[0011] The composite magnesium cement and alkali-activated slag road surface rapid repair mortar also includes fine aggregate and admixture.
[0012] As a possible implementation manner, further, the fine aggregate is a wear-resistant material, and the admixture includes nanocellulose and a water reducing agent.
[0013] As a possible implementation manner, further, the composite magnesium cement and alkali-activated slag road surface rapid repair mortar comprises, by weight:
[0014] 40-50 parts of dead-burned magnesium oxide, 10-15 parts of dipotassium hydrogen phosphate, 3-6 parts of disodium hydrogen phosphate, 20-30 parts of domestic waste incineration slag, 4-6 parts of nano-colloidal silica, 18-24 parts of water, 60-80 parts of fine aggregate, 0.2-0.4 parts of nano-cellulose, and 2-4 parts of water reducing agent.
[0015] As a possible implementation, further, the nano-colloidal silica is a transparent liquid, SiO2 solid content: 30±1wt%, and its physical performance indicators are viscosity: 7mPa.s, density: 1.21-1.29g / cm 3 , particle size: 10~20nm, pH value: 9~10.
[0016] As a possible implementation mode, further, the domestic waste incineration slag is powder particles obtained by screening out unburned waste from the slag bottom ash, drying at 100° C. for 24 hours, and finally ball milling; the particle size is above 200 meshes, and the MgO content is ≥5wt%.
[0017] As a possible implementation manner, further, the fine aggregate is one or more of wear-resistant materials such as corundum, quartz sand and steel slag.
[0018] As a preferred embodiment, preferably, the nanocellulose is cellulose nanocrystals with an average diameter of 20 nm and a length of 100 nm to 1 μm.
[0019] The present invention also provides a method for preparing a magnesium phosphate cementitious material road surface rapid repair mortar, comprising the following steps:
[0020] 1) dissolving dipotassium hydrogen phosphate and disodium hydrogen phosphate in half of the added water to form a phosphate solution for later use;
[0021] 2) dissolving the nano-colloidal silica, nano-cellulose and water reducing agent in the remaining half of the added water, and performing ultrasonic dispersion using an ultrasonic dispersant to form an additive solution;
[0022] 3) adding the dead-burned magnesium oxide, the slag from the incineration of domestic waste and the fine aggregate into a stirring pot and mixing them thoroughly and evenly to form a mixture;
[0023] 4) After adding the phosphate solution in step 1) to the mixture in step 3), stirring slowly for 1 minute, add the admixture solution in step 2), continue stirring slowly for 1 minute, and finally stir quickly for 1 minute to obtain a rapid road repair mortar.
[0024] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0025] 1) The present invention utilizes the hydration intermediates (potassium hydroxide and sodium hydroxide) of magnesium phosphate gelling materials to react with nano-colloidal silica to generate potassium silicate and sodium silicate (2KOH+SiO2→K2SiO3+H2O, 2NaOH+SiO2→Na2SiO3+H2O), thereby stimulating the slag from the incineration of domestic waste to generate a highly water-resistant CASH gel. This not only effectively utilizes the slag from the incineration of domestic waste, practices the concept of green and environmentally friendly development, but also improves the water resistance of magnesium phosphate gelling materials. In addition, the magnesium oxide content in the incineration slag of domestic waste is relatively high, which can reduce the use of dead-burned magnesium oxide, thereby reducing costs, and the magnesium phosphate gelling material is resistant to harmful heavy metals (such as Pb 2+ , Cu 2+ , Hg 2+ 、Cd 2+ and Cr 3+ It has a good solidification effect and can effectively prevent the heavy metals in the slag from seeping out and polluting the environment during the incineration of domestic waste.
[0026] 2) When magnesium phosphate cementitious material uses dipotassium hydrogen phosphate or disodium hydrogen phosphate as the alkaline solution, as the potassium hydroxide or sodium hydroxide generated by the reaction increases, the hydration reaction will be inhibited, that is, the hydration reaction rate of the cement is reduced, thereby prolonging the setting time of the cement, but also resulting in poor early strength. However, the present invention, by adding nano-colloidal silica, can react with the intermediate products potassium silicate and sodium silicate, thereby promoting further reaction of magnesium phosphate cementitious cement, and can effectively control the setting time of cement and improve the early strength of cement.
[0027] 3) The present invention not only utilizes the high water absorption property of nanocellulose to supplement water for the later secondary hydration, but also can reduce the shrinkage of mortar through internal curing and improve the volume stability of mortar. In addition, nanofibers themselves have high tensile strength, high elastic modulus, bridging effect and nano effect, which can improve the mortar's anti-bending performance, compression performance, crack resistance and anti-seepage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is the softening coefficient of magnesium phosphate cement mortar of comparative example 1-3 and embodiment 1-3 after natural curing for 28 days and then soaking in water for 28 days. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] The invention provides a composite magnesium cement and alkali-activated slag road surface rapid repair mortar, which is composed of the following raw materials in parts by weight: 40-50 parts of dead-burned magnesium oxide, 10-15 parts of dipotassium hydrogen phosphate, 3-6 parts of disodium hydrogen phosphate, 20-30 parts of domestic waste incineration slag, 4-6 parts of nano-colloidal silica, 60-80 parts of fine aggregate, 18-24 parts of water, 0.2-0.4 parts of nano-cellulose and 2-4 parts of water reducing agent.
[0032] Among them, nano-colloidal silica is a transparent liquid with a SiO2 solid content of 30±1wt%. Its physical properties are viscosity: 7mPa.s, density: 1.21~1.29g / cm 3 , particle size: 10-20nm, pH value: 9-10. The slag from the incineration of domestic waste is powdered particles obtained by screening out the unburned waste from the bottom ash of the slag, drying it at 100℃ for 24h, and finally ball milling it. The particle size is above 200 meshes, and the MgO content is ≥5wt%. The fine aggregate is one or more wear-resistant materials such as corundum, quartz sand and steel slag; the nanocellulose is cellulose nanocrystals with an average diameter of 20nm and a length of 100nm-1μm.
[0033] A method for preparing a road surface rapid repair mortar of composite magnesium cement and alkali-activated slag comprises the following steps:
[0034] 1) Dissolve 10-15 parts of dipotassium hydrogen phosphate and 3-6 parts of disodium hydrogen phosphate in half of the added water to form a phosphate solution for later use.
[0035] 2) Dissolve 4-6 parts of nano-colloidal silica, 0.2-0.4 parts of nano-cellulose and 2-4 parts of water reducing agent in the remaining half of the added water, and perform ultrasonic dispersion using an ultrasonic dispersant to form an additive solution.
[0036] 3) Add 40-50 parts of dead-burned magnesium oxide, 20-30 parts of domestic waste incineration slag and 60-80 parts of fine aggregate into a stirring pot, mix them thoroughly, and stir them evenly to form a mixture.
[0037] 4) After adding the phosphate solution in step 1) to the mixture in step 3), stirring slowly for 1 minute, add the admixture solution in step 2), continue stirring slowly for 1 minute, and finally stir quickly for 1 minute to obtain a rapid road repair mortar.
[0038] Example 1
[0039] The composite magnesium cement and alkali-activated slag road rapid repair mortar in this embodiment is composed of the following raw materials in parts by weight: 50 parts of dead-burned magnesium oxide, 15 parts of dipotassium hydrogen phosphate, 6 parts of disodium hydrogen phosphate, 20 parts of domestic waste incineration slag, 4 parts of nano-colloidal silica, 60 parts of fine aggregate, 18 parts of water, 0.2 parts of nano-cellulose and 2 parts of water reducer. The preparation process is as follows:
[0040] 1) Dissolve 15 parts of dipotassium hydrogen phosphate and 6 parts of disodium hydrogen phosphate in 9 parts of water to form a phosphate solution for later use.
[0041] 2) 4 parts of nano-colloidal silica, 0.2 parts of nano-cellulose and 2 parts of water reducing agent are dissolved in the remaining 9 parts of water, and ultrasonic dispersion is performed using an ultrasonic dispersant to form an additive solution.
[0042] 3) Add 50 parts of dead-burned magnesium oxide, 20 parts of domestic waste incineration slag and 60 parts of fine aggregate into a stirring pot, mix them thoroughly, and stir them evenly to form a mixture.
[0043] 4) Add the phosphate solution in 1) to the mixture in 3) and stir slowly for 1 minute, then add the admixture solution in 2), continue to stir slowly for 1 minute, and finally stir quickly for 1 minute to obtain a quick road repair mortar.
[0044] Example 2
[0045] The composite magnesium cement and alkali-activated slag road rapid repair mortar in this embodiment is composed of the following raw materials in parts by weight: 40 parts of dead-burned magnesium oxide, 12 parts of dipotassium hydrogen phosphate, 4 parts of disodium hydrogen phosphate, 20 parts of domestic waste incineration slag, 5 parts of nano-colloidal silica, 60 parts of fine aggregate, 20 parts of water, 0.3 parts of nano-cellulose and 2 parts of water reducer. The preparation process is as follows:
[0046] 1) Dissolve 12 parts of dipotassium hydrogen phosphate and 4 parts of disodium hydrogen phosphate in 10 parts of water to form a phosphate solution for later use.
[0047] 2) Dissolve 5 parts of nano-colloidal silica, 0.3 parts of nano-cellulose and 2 parts of water reducing agent in the remaining 10 parts of water, and perform ultrasonic dispersion using an ultrasonic dispersant to form an additive solution.
[0048] 3) Add 40 parts of dead-burned magnesium oxide, 20 parts of domestic waste incineration slag and 60 parts of fine aggregate into a stirring pot, mix them thoroughly, and stir them evenly to form a mixture.
[0049] 4) Add the phosphate solution in 1) to the mixture in 3) and stir slowly for 1 minute, then add the admixture solution in 2), continue to stir slowly for 1 minute, and finally stir quickly for 1 minute to obtain a quick road repair mortar.
[0050] Example 3
[0051] The composite magnesium cement and alkali-activated slag road rapid repair mortar in this embodiment is composed of the following raw materials in parts by weight: 40 parts of dead-burned magnesium oxide, 12 parts of dipotassium hydrogen phosphate, 4 parts of disodium hydrogen phosphate, 30 parts of domestic waste incineration slag, 6 parts of nano-colloidal silica, 70 parts of fine aggregate, 24 parts of water, 0.4 parts of nano-cellulose and 4 parts of water reducer. The preparation process is as follows:
[0052] 1) Dissolve 15 parts of dipotassium hydrogen phosphate and 5 parts of disodium hydrogen phosphate in 12 parts of water to form a phosphate solution for later use.
[0053] 2) 6 parts of nano-colloidal silica, 0.4 parts of nano-cellulose and 4 parts of water reducing agent are dissolved in the remaining 12 parts of water, and ultrasonic dispersion is performed using an ultrasonic dispersant to form an additive solution.
[0054] 3) Add 40 parts of dead-burned magnesium oxide, 30 parts of domestic waste incineration slag and 70 parts of fine aggregate into a stirring pot, mix them thoroughly, and stir them evenly to form a mixture.
[0055] 4) Add the phosphate solution in 1) to the mixture in 3) and stir slowly for 1 minute, then add the admixture solution in 2), continue to stir slowly for 1 minute, and finally stir quickly for 1 minute to obtain a quick road repair mortar.
[0056] Comparative Example 1
[0057] Weigh 50 parts of dead-burned magnesium oxide, 15 parts of dipotassium hydrogen phosphate, 6 parts of disodium hydrogen phosphate, 4 parts of nano-colloidal silica, 60 parts of fine aggregate, 18 parts of water, 0.2 parts of nano-cellulose and 2 parts of water reducer. The preparation process is as follows:
[0058] 1) Dissolve 15 parts of dipotassium hydrogen phosphate and 6 parts of disodium hydrogen phosphate in 9 parts of water to form a phosphate solution for later use.
[0059] 2) 4 parts of nano-colloidal silica, 0.2 parts of nano-cellulose and 2 parts of water reducing agent are dissolved in the remaining 9 parts of water, and ultrasonic dispersion is performed using an ultrasonic dispersant to form an additive solution.
[0060] 3) Add 50 parts of dead-burned magnesium oxide and 60 parts of fine aggregate into a mixing pot and mix thoroughly and evenly to form a mixture.
[0061] 4) Add the phosphate solution in 1) to the mixture in 3) and stir slowly for 1 minute, then add the admixture solution in 2), continue to stir slowly for 1 minute, and finally stir quickly for 1 minute to obtain a quick road repair mortar.
[0062] Comparative Example 2
[0063] Weigh 40 parts of dead-burned magnesium oxide, 12 parts of dipotassium hydrogen phosphate, 4 parts of disodium hydrogen phosphate, 20 parts of domestic waste incineration slag, 60 parts of fine aggregate, 20 parts of water, 0.2 parts of nanocellulose and 2 parts of water reducing agent. The preparation process is as follows:
[0064] 1) Dissolve 12 parts of dipotassium hydrogen phosphate and 4 parts of disodium hydrogen phosphate in 10 parts of water to form a phosphate solution for later use.
[0065] 2) 0.3 parts of nanocellulose and 2 parts of water reducing agent are dissolved in the remaining 10 parts of water, and ultrasonic dispersion is performed using an ultrasonic dispersant to form an additive solution.
[0066] 3) Add 40 parts of dead-burned magnesium oxide, 20 parts of domestic waste incineration slag and 60 parts of fine aggregate into a stirring pot, mix them thoroughly, and stir them evenly to form a mixture.
[0067] 4) Add the phosphate solution in 1) to the mixture in 3) and stir slowly for 1 minute, then add the admixture solution in 2), continue to stir slowly for 1 minute, and finally stir quickly for 1 minute to obtain a quick road repair mortar.
[0068] Comparative Example 3
[0069] Weigh 40 parts of dead-burned magnesium oxide, 14 parts of dipotassium hydrogen phosphate, 4 parts of disodium hydrogen phosphate, 30 parts of domestic waste incineration slag, 6 parts of nano-colloidal silica, 70 parts of fine aggregate, 24 parts of water and 4 parts of water reducer. The preparation process is as follows:
[0070] 1) Dissolve 15 parts of dipotassium hydrogen phosphate and 5 parts of disodium hydrogen phosphate in 12 parts of water to form a phosphate solution for later use.
[0071] 2) 6 parts of nano-colloidal silica and 4 parts of water reducing agent are dissolved in the remaining 12 parts of water, and ultrasonic dispersion is performed using an ultrasonic dispersant to form an additive solution.
[0072] 3) Add 40 parts of dead-burned magnesium oxide, 30 parts of domestic waste incineration slag and 70 parts of fine aggregate into a stirring pot, mix them thoroughly, and stir them evenly to form a mixture.
[0073] 4) Add the phosphate solution in 1) to the mixture in 3) and stir slowly for 1 minute, then add the admixture solution in 2), continue to stir slowly for 1 minute, and finally stir quickly for 1 minute to obtain a quick road repair mortar.
[0074] Experimental results analysis
[0075] 1. Mechanical properties
[0076] 1.1) The compressive strength and flexural strength of the magnesium phosphate cement mortar prepared by natural curing for 1 day, 3 days and 28 days in Examples 1-3 and Comparative Examples 1-3, and the compressive strength and flexural strength of the mortar prepared by natural curing for 28 days and then soaking in water for 28 days were tested. The test results are shown in Table 1 below:
[0077] Table 1 Compressive strength and flexural strength of magnesium phosphate cementitious material road rapid repair mortar (MPa)
[0078]
[0079] As can be seen from Table 1 above, the magnitude of the compressive strength and flexural strength (28d) is Comparative Example 1> Example 1> Example 2> Example 3. This indicates that as the amount of slag from the incineration of domestic waste increases, the compressive and flexural strengths of the mortar decrease, especially the early strength, but as the age increases, the downward trend will gradually decrease. Comparative Example 2 and Comparative Example 2 show that the addition of nano-colloidal silica can significantly increase the compressive and flexural strengths of the mortar. Comparative Example 3 and Comparative Example 3 also show that the addition of nanocellulose can also increase the compressive and flexural strengths of the mortar.
[0080] 1.2) The tensile bond strength of magnesium phosphate cement mortar prepared by natural curing for 1d, 3d and 28d in Examples 1-3 and Comparative Examples 1-3 was tested. The test results are shown in Table 2 below:
[0081] Table 2 Tensile bond strength of magnesium phosphate cementitious material pavement rapid repair mortar (MPa)
[0082]
[0083] As can be seen from Table 2 above, the magnitude of the tensile bond strength (28d) is Comparative Example 1> Example 1> Example 2> Example 3, which is consistent with the trend of changes in compressive and flexural strength. This indicates that as the amount of slag from the incineration of domestic waste increases, the tensile bond strength of the mortar will decrease to a certain extent, but it can still maintain a high level (the lowest 28d tensile bond strength of Example 3 is still 3.47MPa, meeting the construction requirements). Similarly, by comparing Example 2 with Comparative Example 2, and Example 3 with Comparative Example 3, it is found that the tensile bond strength of the mortar can be significantly increased by adding nano-colloidal silica and nano-cellulose.
[0084] 2. Setting time
[0085] According to GB / 1346-2011 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency", the initial setting and final setting times of the magnesium phosphate cement pastes prepared in Examples 1-3 and Comparative Examples 1-3 were measured using a Vicat instrument. The test results are shown in Table 3 below:
[0086] Table 3 Setting time of magnesium phosphate cementitious material road quick repair mortar
[0087]
[0088]
[0089] As can be seen from Table 3 above, the setting time is Comparative Example 1 < Example 1 < Example 2 < Example 3. This shows that adding domestic waste incineration slag can effectively delay the setting time of cement, and as the amount of domestic waste incineration increases, the retarding effect becomes more obvious. On the contrary, as the setting time of Example 2 is significantly shorter than that of Comparative Example 2, it can be seen that the setting time of magnesium phosphate cement can be significantly shortened by adding nano-colloidal silica.
[0090] 3. Water resistance
[0091] Attached Figure 1 is the softening coefficient of magnesium phosphate cement mortar after natural curing for 28 days and then soaking in water for 28 days in Comparative Example 1 and Examples 1-3 (softening coefficient (28 days) = compressive strength after natural curing for 28 days and then soaking in water for 28 days / compressive strength after natural curing for 28 days). Figure 1 It can be seen that the softening coefficient is Comparative Example 1 < Example 1 < Example 2 < Example 3, indicating that the addition of domestic waste incineration slag can effectively improve the water resistance of magnesium phosphate cement mortar, and as the amount of domestic waste incineration slag increases, the improvement effect becomes more obvious. In addition, by comparing Comparative Example 2 with Example 2 and Comparative Example 3 with Example 3, it can also be found that the addition of nano-colloidal silica and nano-cellulose can improve the water resistance of magnesium phosphate cement mortar.
[0092] 4. Crack resistance
[0093] Reference (Ji Tao, Zhang Binbin, Chen Yongbo, Zhuang Yizhou. An evaluation method of cracking resistance of lightweight aggregate concrete[J]. Journal of Central South University (English Edition), 2014, 21(4): 1607-1615).
[0094] The test results are as follows: the crack resistance evaluation index (A cr ) were 2.39, 2.04, 1.86 and 1.73 respectively. Since the mortar ring test results only had an upward curve during the test period, its A cr The smaller the value of , the better the crack resistance. It can be seen that compared with Comparative Example 3 (without nanocellulose), the A cr are all small, indicating that the crack resistance of mortar can be improved by adding nanocellulose, and the higher the dosage, the better the effect.
[0095] In summary, the raw material composition of the rapid pavement repair mortar of composite magnesium cement and alkali-activated slag is preferably: 50 parts of dead-burned magnesium oxide, 15 parts of dipotassium hydrogen phosphate, 6 parts of disodium hydrogen phosphate, 20 parts of domestic waste incineration slag, 4 parts of nano-colloidal silica, 60 parts of fine aggregate, 18 parts of water, 0.2 parts of nano-cellulose, and 2 parts of water reducer.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite magnesium cement and alkali-activated slag road surface rapid repair mortar, characterized in that: The composite magnesium cement and alkali-activated slag road surface rapid repair mortar uses a composite system of magnesium phosphate cementitious material and alkali-activated cementitious material as a cementitious material; The magnesium phosphate gelling material is composed of dead-burned magnesium oxide, dipotassium hydrogen phosphate and disodium hydrogen phosphate; The alkali-activated gelling material is composed of potassium silicate and sodium silicate generated by the reaction of the hydration intermediate product of the slag from the incineration of domestic waste and the magnesium phosphate gelling material with nano-colloidal silica; the nano-colloidal silica is a transparent liquid with a SiO2 solid content of 30±1wt%, and its physical performance indicators are viscosity: 7mPa.s, density: 1.21-1.29g / cm 3 , particle size: 10-20nm, pH value: 9-10; The composite magnesium cement and alkali-activated slag road surface rapid repair mortar also includes fine aggregate and admixtures, and the admixtures include nanocellulose and a water reducing agent; The composite magnesium cement and alkali-activated slag road surface rapid repair mortar comprises, by weight: 40-50 parts of dead-burned magnesium oxide, 10-15 parts of dipotassium hydrogen phosphate, 3-6 parts of disodium hydrogen phosphate, 20-30 parts of domestic waste incineration slag, 4-6 parts of nano-colloidal silica, 18-24 parts of water, 60-80 parts of fine aggregate, 0.2-0.4 parts of nano-cellulose, and 2-4 parts of water reducing agent; The domestic waste incineration slag is powdered particles obtained by screening out unburned waste from the slag bottom ash, drying at 100° C. for 24 hours, and finally ball milling. The particle size is above 200 meshes, and the MgO content is ≥5wt%.
2. The rapid road repair mortar of composite magnesium cement and alkali-activated slag according to claim 1, characterized in that: The fine aggregate is a wear-resistant material.
3. The rapid road repair mortar of composite magnesium cement and alkali-activated slag according to claim 1, characterized in that: The fine aggregate is one or more of corundum, quartz sand and steel slag.
4. The rapid road repair mortar of composite magnesium cement and alkali-activated slag according to claim 1, characterized in that: The nanocellulose is cellulose nanocrystals with an average diameter of 20 nm and a length of 100 nm to 1 μm.
5. A method for preparing a rapid road repair mortar of composite magnesium cement and alkali-activated slag according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) dissolving dipotassium hydrogen phosphate and disodium hydrogen phosphate in half of the added water to form a phosphate solution for later use; 2) dissolving the nano-colloidal silica, nano-cellulose and water reducing agent in the remaining half of the added water, and performing ultrasonic dispersion using an ultrasonic dispersant to form an additive solution; 3) adding the dead-burned magnesium oxide, the slag from the incineration of domestic waste and the fine aggregate into a stirring pot and mixing them thoroughly and evenly to form a mixture; 4) After adding the phosphate solution in step 1) to the mixture in step 3), stirring slowly for 1 minute, add the admixture solution in step 2), continue stirring slowly for 1 minute, and finally stir quickly for 1 minute to obtain a rapid road repair mortar.
Citation Information
Patent Citations
A fast-hardening, early-strength, high-water-resistant magnesium phosphate-alkali-activated hybrid cementitious material
CN113816635B
Water-resistant magnesium phosphate cement and preparation method thereof
CN115818993A
Rapid repairing material based on magnesium phosphate cement-based sulfate-resistant coating and preparation method
CN113045285A
Preparation process of alkali-activated cementing material for waste incineration bottom ash treatment
CN114315188A